Utilization of Information Technology Media at Pertiwi Ajibarang Wetan Kindergarten - Sugiarti, Sugiarti; Aryani, Ine Kusuma (Proceedings Series on Social Sciences & Humanities, 2025)
Study This aiming For describe utilization of technology media information in learning child age early in Pertiwi Ajibarang Kindergarten Wetan. The method used is study qualitative descriptive with technique data collection through observation, interviews, and documentation. Subjects study consists of from three teachers and four tens participant educate. Research results show that the teacher has utilizing technology media information like projectors, educational videos, and applications digital learning in activity learning. Use of this media capable increase interest and participation active child during activity ongoing. However Thus, the challenges faced covering limitations device technology and still low digital literacy of teachers. Therefore that, is needed support training and facilities supporters for utilization technology can more optimal and precise target in the learning process at the PAUD level.